Family Planning as a Cross-cutting Issue in Development Programmes - Bultasová, Denisa; Kváča, Vladimír, 1977-; Balcha, Daniel Messele; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2012)
This thesis focuses on integration of family planning into development programmes. It aims to recommend most appropriate ways that non-governmental organizations can adopt in order to introduce family planning as a cross-cutting issue in their development programmes in rural regions of Ethiopia. This is to ensure that women and men have the possibility to make free and informed choices on their childbearing preferences and exercise family planning. In order to identify the most suitable approaches, methods and strategies for family planning mainstreaming, the thesis determines the most significant determinants and factors that affect the childbearing preferences and identify those that can be addressed by family planning mainstreaming. The thesis bases its theoretical framework on the Amartya Sen's Capabilites approach to human development. The second part of the thesis is dedicated to Ethiopia Case Study.
Vedoucí práce: Vladimír Kváča
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: mezinárodní politika a diplomacie [obor dipl. práce]; diplomové práce; master's theses